Acmaeoderella rejzeki, a new species of jewel-beetles from Crete with notes on the species-group composition of the subgenus Omphalothorax Volkovitsh, 1979 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini) - M.G. Volkovitsh (Кавказский энтомологический бюллетень, 2018)
Acmaeoderella (Omphalothorax) rejzeki sp. n. from the Crete Island (Greece) is described, illustrated and compared with closely related A. despecta (Baudi di Selve, 1870). Species-groups adspersula and despecta are established within the subgenus Omphalothorax and a list of species attributed to this subgenus is presented.